EFFECT OF HEAT TREATMENT TEMPERATURE ON THE FORMATION OF DUAL PHASE STEEL AISI 1005 HARDNESS AND FLEXURE STRENGTH CHARACTERISTICS OF MATERIALS - Kris Witono; Lisa Agustriyana; Agus Setiawan (Universitas Lambung Mangkurat, 2015)
Any material intended for automotive use, especially in the body panels must have the criteria able to form (formable), weldability (weldable), coatable (resistant to corrosion) and able to be repaired (repairable). One group of materials that meet all the above requirements are dual phase steel. To form a dual phase steel can be done through a process of heat treatment.The purpose of this study was to determine the effect of heat treatment temperature on the formation of a dual phase of the material hardness properties and flexural strength steel.The method used is a variation of the process of heat treatment at temperature 7300C, 7500C, 7700C, 8000C, 8500C, 9000C.The results of the study include the establishment of dual phase steel can improve the hardness of AISI 1005 steel with a carbon content of 0.033% C, the highest value of flexural strength is obtained at a temperature of 770 ° C treatment that is 1.98 kg / mm2 with 223.08 HV hardness values. The hardness and flexural lowest strength obtained at the treatment temperature of 900 ° C is 197.14 HV and 1.15 kg / mm2 and dual phase steel with optimum mechanical properties obtained at a temperature of 770 ° C. Key word : heat treatment, dual phase, hardness, flexure strength